Manejo da fertilidade em solos degradados e seus efeitos sobre as trajetórias iniciais da comunidade e a plasticidade funcional de espécies nativas na restauração florestal por semeadura direta - Mariano, Lucas Florêncio (Universidade Federal de São Carlos, 2026)
Forest restoration through direct seeding is a low-cost alternative for recovering degraded areas; however, it is often limited by poor initial seedling establishment. This thesis investigated how soil fertility management, through liming and the application of organic and mineral fertilizers, influences the performance, nutrition, and organization of 37 native species in the Atlantic Forest under ecological restoration by direct seeding. Two experiments were conducted: a field experiment evaluating two levels of base saturation (V% = 25% and 50%) and three fertilization treatments (NPK 4-14-8, organic fertilizer - poultry litter, and a non-fertilized control) in soil previously abandoned and invaded by grasses; and a greenhouse experiment testing three levels of base saturation (V% = 3%, 25%, and 50%) and the same fertilization treatments, aiming to assess the nutritional response and plasticity of 13 tree species under degraded cut-slope soil conditions. The results showed that fertility management significantly altered soil chemical attributes, such as pH, exchangeable aluminum, and exchangeable bases, directly affecting species growth and establishment. The combination of liming with organic and mineral fertilization was more effective than isolated applications, promoting greater initial growth and improved community organization. However, responses varied among species, reflecting differences in ecological strategies and plasticity. It is concluded that soil correction and fertilization strategies adapted to species heterogeneity are essential to improve forest restoration success and to promote more resilient and functional communities in the long term.
Fertility management in degraded soils and its effects on the initial trajectories of the community and the functional plasticity of native species in forest restoration by direct seeding
Keywords: Restauração ecológica; Semeadura direta; Fertilidade do solo; Nutrição de plantas; Ecological restoration; Direct seeding; Soil fertility; Plant nutrition; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::FLORESTAMENTO E REFLORESTAMENTO; 15. Vida Terrestre